Avaliação voltamétrica dos íons metálicos (Cobre, Cádmio e Chumbo) em amostras de combustíveis previamente digeridas em microondas usando eletrodo quimicamente modificado por sais tetrazólios - MOREIRA, Lucy Rose de Maria Oliveira (2010)
This paper describes an analytical procedure for determination of trace metals copper, cadmium and lead in fuel samples, using Basal Plane Pyrolytic Graphite Modified Electrode (BPPGME) by tetrazolium salts: ([3,3 '- (3-3'-dimethoxy-4, bifenililen 4'-bis [2 - (4-nitrophenyl)-5-phenyl-2H-tetrazolium (NBT) Cl 3 - (4,5 - dimetitiazol-2il) -2,5-diphenyl-2H-Tetrazolium ( MTT) Br]. Samples of fuels (ethanol, biodiesel and gasoline) were previously digested in a microwave oven using nitric acid media and peroxides (biodiesel) and only nitric acid (alcohol and gasoline). The species of tetrazolium employed adsorbed spontaneously and irreversibly at the electrode surface and showed redox peaks characteristic of pH dependent. The metal ions studied reacted at the electrode surface chemically modified to produce marked changes in the corresponding voltammograms. Peak current produced in the voltammograms using Chemically Modified Electrode in the presence of metallic ion was used for quantification of metal in the sample of fuel. In order to determine the species of interest the best results were in pH 5.0 for copper and pH 6.0 for other species. The concentration range for copper was 2,0x10-6 to 1.25x10-5 mol L-1; and for cadmium and lead the range varied from 1,0x10-9 to 1,0x10-8 mol L-1. The limit of detection in samples fuels (ethanol, biodiesel or petrol), by VRA was 2,5x10-6 mol L-1. The accuracy of the proposed technique (VRA) for the determination of copper in ethanol, biodiesel and gasoline was compared with the emission spectroscopy technique Optical inductively coupled plasma (ICP-OES), providing results in agreement among themselves, i.e. the copper concentration in the samples analyzed by both techniques to a level of certainty of 95%, not statistically different.